Functionalized injection type bionic hydrogel for promoting bone healing and preparation method thereof

By combining ultrasonic-controlled drug-release microspheres, functional calcium carbonate porous microspheres, nanoclays and magnetic nanoparticles in bone healing materials, the problem of unstable release of bone healing materials and mismatch of bone regeneration speed is achieved, and bone is achieved Drug release control and bone regeneration efficiency during healing reduce the risk of infection and pain.

CN119280487AInactive Publication Date: 2025-01-10SHANDONG BRANDEN MEDICAL DEVICE

Patent Information

Application Number
CN202411850982.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing bone healing materials cannot effectively match bone healing and regeneration speeds, resulting in non-healing or delayed healing of fractures, and problems of instability in drug release, risk of toxicity and secondary trauma.

Method used

Develop a functional injection-type bionic hydrogel containing ultrasonic-controlled drug-release microspheres, functional calcium carbonate porous microspheres, nanoclays, calcium phosphate bone cement and magnetic nanoparticles. It is prepared by adjusting the composition ratio and process to achieve Differentiated degradation rate and drug release control provide healthy microenvironment homeostasis and mechanical support.

Benefits of technology

It realizes the controllability and stability of drug release during bone healing, reduces high reactive oxygen levels, promotes bone cell growth and angiogenesis, improves bone regeneration efficiency, reduces infection and pain, and is in line with the variety of modern orthopedic treatments. Demand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280487A_ABST
    Figure CN119280487A_ABST
Patent Text Reader

Abstract

The invention discloses functional injection type bionic hydrogel for promoting bone healing and a preparation method thereof, and relates to the technical field of medical instruments. The hydrogel has good functional characteristics, is a biomimetic material prepared on the basis of methacrylated gelatin, and aims to regulate and control the degradation rate, the drug release mechanism and diversified synergistic treatment and promote bone repair and regeneration; according to the hydrogel, matching of the degradation rate and the bone regeneration rate is achieved through reasonable matching, stem cell osteogenic differentiation and angiogenesis are promoted, ultrasonic controlled-release drug release and synergistic controlled-release of active factors are achieved, inflammation is reduced, and the bone repair process is promoted; the calcium phosphate bone cement provides biocompatibility and bone conductivity, and the nano clay releases active ions to improve the microenvironment and promote bone repair; in addition, the magnetic nanoparticles and a static magnetic field have synergistic interaction, the bone healing process is further accelerated, and treatment effect monitoring is enhanced through magnetic resonance imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical devices, and in particular to a functional injectable bionic hydrogel for promoting bone healing and a preparation method thereof. Background Art

[0002] Fractures are one of the most common injuries of the musculoskeletal system. Despite extensive progress in treatment development in recent years, the nonunion rate still accounts for about 5-10% of total fractures, which can lead to the formation of irregular bone defects and seriously affect the patient's life. So far, fracture nonunion and bone defects remain a challenge for orthopedic surgeons.

[0003] Bone healing is a complex physiological process, including acute inflammation, recruitment of bone marrow mesenchymal stem cells, primary cartilage callus formation, angiogenesis and bone remodeling. The main methods for treating fractures are traditional Chinese medicine and Western medicine. Western medicine often uses plaster wrapping, steel plate and steel nail fixation, surgery, injection and drip, etc. Although these methods can stabilize the fracture site, they usually have problems such as slow healing, incomplete functional recovery and many complications. The patient suffers a lot, the course of treatment is long, the cost of treatment is high, and the surgery will cause other soft tissue damage to the human body, and a second surgery is required. Especially in complex fractures, elderly patients or osteoporosis patients, the process of bone healing may be affected by more factors, resulting in delayed or non-union of bone healing, which seriously affects the patient's quality of life. The existing traditional Chinese medicine treatment scheme adopts the method of reduction, oral Chinese medicine plus external plaster, which has a certain effect on fracture healing, but the drug reaches the lesion through the digestive tract and blood circulation, and the control of symptoms is slow and the effect is poor, and it is easy to hurt the spleen and stomach, and does not shorten the course of the patient and the pain period. The external plaster contains toxic lead, which is harmful to the human body.

[0004] For the treatment of patients who have formed irregular bone defects due to nonunion of fractures, autologous grafts remain the gold standard for bone substitutes because they have ideal osteogenic properties while maintaining complete tissue compatibility. However, autologous grafts are limited in supply and have high donor site morbidity. At the same time, allogeneic grafts also have the risk of poor osteogenicity, immune rejection, and infection transmission. In addition, current bone biomaterials, such as titanium alloys, bioceramics, and PEEK, are mostly substitutes for bone defects. Due to insufficient osteogenic capacity and poor biodegradability, they cannot induce functional bone regeneration in situ. At the same time, biodegradable materials can induce partial bone regeneration, but due to various reasons such as the mismatch between the degradation rate and the bone healing regeneration rate, low bioactivity, poor porosity, and toxicity of degradation products, full-segment bone reconstruction cannot be achieved. The emergence of enhanced recovery after surgery (ERAS) has put forward new requirements for orthopedic surgeons, that is, to use appropriate materials to minimize surgical trauma, but the implantation of traditional bone substitute materials through open surgery will cause secondary trauma, pain, and dysfunction, which does not meet the requirements of ERAS. In addition, prolonged and inadequate inflammatory responses often lead to impaired and delayed bone repair processes, while high reactive oxygen levels are the main reason hindering the bone repair process.

[0005] With the continuous development of biomaterials and regenerative medicine, injectable hydrogels, as a material with good biocompatibility, adjustable mechanical properties and biodegradability, have gradually become a research hotspot for bone repair and regeneration. In addition, injectable hydrogels have the potential to be implanted through minimally invasive surgery and are able to penetrate deeply through tiny channels, which is considered a viable alternative to traditional open surgery. However, currently injectable hydrogels are mainly organic biomaterials, which can cause local accumulation of degradation waste, affect endogenous cell bioactivity, and impair tissue regeneration. Therefore, innovative methods are needed to meet the requirements of ERAS and benefit patients, especially to promote fracture healing and treat irregular bone defects.

[0006] In order to solve the above problems, various improvement methods have been proposed. Existing patent CN 118078739 A discloses a hydrogel that promotes the healing of skull defects, its preparation method and application. The hydrogel has excellent mechanical properties and promotes angiogenesis and bone regeneration, but the release rate of its drugs or active substances is not suitable. It is released autonomously and quickly before 12 hours, and the subsequent release is a slow and gradual process. The cumulative release rate reaches more than 50% within 168 hours, which does not match the progress of bone repair and there is a risk that the drug or active substance has been consumed before the middle or late stage of bone healing. At the same time, the autonomous rapid release will not be controlled by the doctor, and there is a risk of excessive drug dosage and drug poisoning.

[0007] CN 114931670 B discloses an injectable, self-healing hydrogel for bone repair, and a preparation method and application thereof. The hydrogel has good biocompatibility and low cost. However, this design cannot solve the problems arising in the first stage of fracture healing. It is difficult to maintain the steady state of the bone repair microenvironment without drug support, and the drug release process cannot be artificially controlled. The key point is that although this design matches the degradation rate of bone tissue regeneration, it cannot achieve differentiated degradation and cannot be applied to the staged development of bone healing, and there is a risk of affecting the bone healing rate.

[0008] CN 118718104 A discloses a viscoelastic hydrogel complex for promoting bone defect healing, its preparation and application. The hydrogel has excellent viscoelastic mechanical properties and enhances the expression and secretion of TGF-β1 of BMDMs. However, this design cannot meet the requirements of the bone healing stage and bone growth rate, and does not continuously provide materials, structures and spaces for bone cell growth.

[0009] Therefore, it is urgent to develop a new material that can comprehensively solve existing clinical problems to promote bone healing and heal bone defects. The new material should be able to provide a healthy microenvironment homeostasis for bone healing and bone regeneration, reduce high reactive oxygen levels, avoid infection and inflammation, and relieve patient pain. It should also include a framework to ensure the stable and sustained release of drugs or active ingredients, optimize the sustained effect of drugs or active ingredients, and preferably be able to coordinate treatment and repair in multiple aspects (such as magnetic fields, ultrasound, etc.) to adapt to the three stages of bone healing; most importantly, its degradation rate should match the rate of bone healing and regeneration, thereby providing sufficient physical and chemical support and providing space for bone growth. Too early or too slow is not conducive to bone repair. If the degradation rate is too fast, it will not provide enough mechanical support for the bone healing site, nor will the embedded functional substances provide help for the later stage of bone healing. At the same time, it will lead to the accumulation of a large number of degradation products, which will lead to allergic reactions or tissue damage. If the degradation rate is too slow, it may form a certain physical barrier, which limits the space and environment for new bone growth, and it will stay in the body for a long time, affecting the normal metabolism and repair of surrounding tissues, and thus affecting the balance of the repair process. In addition, it is best for the new material to be able to change its shape according to the environment to fit the part to be treated, so as to better accelerate bone repair and treatment. In summary, it is necessary not only to improve the treatment effect, but also to enhance the comfort and safety of patients, but also to meet the growing and diversified needs of modern clinical practice for bone repair, thereby promoting the progress of medical practice. Summary of the invention

[0010] One of the purposes of the present invention is to provide a functional injectable bionic hydrogel that promotes bone healing in order to solve the above problems. The hydrogel has good biodegradability, biocompatibility, adhesion, antioxidant properties, weak magnetism and developability. The hydrogel is a bionic material based on methacrylated gelatin, embedded with 1-5% ultrasonic controlled release drug-loaded microspheres and 1-5% functional calcium carbonate porous microspheres, as well as 5-10% nanoclay, 10-20% calcium phosphate bone cement, 1-5% magnetic nanoparticles and 1-5% peroxidase; the antioxidant property is achieved by the peroxidase in the hydrogel by reducing the high level of active oxygen at the bone healing site; the weak magnetism is achieved by the 1-5% % magnetic nanoparticles are produced, and can cooperate with external magnetism to promote bone healing; the development property refers to the use of magnetic nanoparticles as auxiliary contrast agents in magnetic resonance imaging using their weak magnetism, which makes imaging clearer and convenient for real-time observation and research; the ultrasonic controlled release drug-loaded microspheres are biodegradable microspheres that respond to ultrasound waves of a specific frequency and are prepared by an emulsification process and an ultrasonic voltage spraying process, with a particle size of 5-25 μm; the functional calcium carbonate porous microspheres are loaded microspheres formed by loading active factors into calcium carbonate porous microspheres, with a particle size of 1-13 μm, and can slowly release calcium ions and active factors; the content ratio of the nanoclay and calcium phosphate bone cement in the hydrogel is 1:1-3; To better realize the present invention, further, the ultrasonic voltage spraying process is a technology for preparing microspheres by spraying the emulsion onto the baffle in a synergistic environment of 10-200w ultrasonic wave combined with 6-10kV applied voltage; To better realize the present invention, further, the nano clay is one of montmorillonite, bentonite, kaolin and lattice; To better realize the present invention, further, the active factor is one of bone morphogenetic protein, fibroblast growth factor, platelet-derived growth factor, transforming growth factor β, vascular endothelial growth factor, insulin-like growth factor, chondrocyte growth factor, and extracellular matrix protein.

[0011] The second object of the present invention is to provide a method for preparing a functional injectable biomimetic hydrogel for promoting bone healing, which is carried out according to the following steps: (1) Preparation of ultrasonic controlled release drug-loaded microspheres: 1-5% analgesic and anti-inflammatory drugs and 1-5% emulsifier are added to 10-50% polylactic acid-glycolic acid organic solution, stirred in an ice water environment for 10-20 minutes to obtain an organic phase; then the organic phase is slowly added dropwise to 1-5% polyvinyl alcohol aqueous phase, emulsified for 10-30 minutes under 10-1000w ultrasound and 3000-5000rpm high-speed stirring to obtain an emulsion; the emulsion is placed in a syringe, set a constant flow rate of 0.6-1.4mL / h, an ultrasonic power of 10-200w and an applied voltage of 6-10kV, spray granulation in a nitrogen environment, and collected in a baffle with a distance of 18-22cm from the tip of the syringe nozzle, and vacuum freeze-dried for 24-36h to obtain ultrasonic controlled release drug-loaded microspheres; To better implement the present invention, further, the analgesic and anti-inflammatory drug is one of diclofenac sodium and lidocaine, preferably diclofenac sodium; To better implement the present invention, further, the emulsifier is one of polyvinyl pyrrolidone, Tween-80, and Span-80, preferably polyvinyl pyrrolidone; To better realize the present invention, further, the mass ratio of the analgesic and anti-inflammatory drug to polylactic acid-glycolic acid is 1:10-50; (2) Preparation of functional porous calcium carbonate microspheres: 30-40% anhydrous sodium carbonate solution and 30-40% calcium chloride solution were added in a volume ratio of 1:1, ultrasonically stirred at 10-1000w for 10-20min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed 3 times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; the porous calcium carbonate microspheres and active factors were added to PBS (pH 7.4) in a mass ratio of 1000:1-5, gently stirred at 10-1000w in an ice water and nitrogen environment for 24-48h, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres; To better implement the present invention, further, the vacuum freeze-drying time is 24-36h; (3) Preparation of hydrogel: Add nano-clay powder and calcium phosphate bone cement powder in a mass ratio of 1:1-3 to a 5% methacrylated gelatin solution containing 0.25% photoinitiator, and stir gently at 10-500w ultrasonic for 15-25min to obtain a mixed solution a; under gentle stirring conditions, add magnetic nanoparticles, catalase, ultrasound-controlled release drug-loaded microspheres and functional calcium carbonate porous microspheres to the 5% methacrylated gelatin solution containing 0.25% photoinitiator in sequence, and continue to stir gently for 15-25min to obtain a mixed solution b; mix the mixed solution a and the mixed solution b in a volume ratio of 1:0.5-1.5, and continue to stir gently for 15-25min to obtain a mixed solution c; place the mixed solution c under 405nm wavelength blue light for polymerization for 20-40s, and collect to obtain a hydrogel; To better realize the present invention, further, the photoinitiator is phenyl (2,4,6-trimethylbenzoyl) lithium phosphate; To better implement the present invention, further, the mass ratio of the magnetic nanoparticles and catalase added is 1:0.5-1.5; To better realize the present invention, further, the polydopamine methacrylamide is added at a concentration of 0.1-0.5%; To better realize the present invention, further, the mass ratio of the ultrasonic controlled release drug-loaded microspheres and the functional calcium carbonate porous microspheres is 1:0.5-1.5; To better implement the present invention, further, the rotation speed of the gentle stirring is 10-100 rpm; The components used in the present invention are all commercially available products, and their structures and compositions are known to those skilled in the art.

[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. Differentiated degradation rate, controllable matching of bone repair process: Nanoclay degrades faster, while calcium phosphate cement degrades slower. By adjusting the composition ratio of nanoclay / calcium phosphate cement to control the degradation rate of the composite hydrogel, it can be matched with the bone regeneration rate to achieve differentiated biodegradation; it is beneficial to promote osteogenic differentiation of stem cells and enhance neovascularization; 2. Take advantage of each other's strengths and make up for each other's weaknesses, and synergize to enhance the effect: (1) Calcium phosphate bone cement has good biocompatibility and bone conductivity, but poor porosity, slow degradation, low bone induction ability, and significantly delayed bone regeneration; the degradation of nanoclay can release active ions such as Mg, Si, and Li, which establish a favorable microenvironment for stem cell osteogenic differentiation and angiogenesis, but its degradation rate is too fast, which does not match the bone regeneration rate, limiting its application in bone regeneration; therefore, take advantage of each other's strengths and make up for each other's weaknesses, and combine calcium phosphate bone cement with nanoclay in hydrogel. The mineralization of the two can form bionic hydroxyapatite crystals with a porous structure, which is conducive to the adhesion and migration of stem cells and osteoblasts, as well as vascular infiltration, promoting bone regeneration; (2) The combined use of magnetic nanoparticles and static magnetic fields is more effective in promoting bone repair and regeneration than the use of magnetic nanoparticles or static magnetic fields alone. On the one hand, it promotes the deposition of calcium at the fracture site, accelerates fracture healing, and promotes the reconstruction of blood circulation and improvement of microcirculation at the fracture site. On the other hand, the magnetic field can activate the CAMP system in the cell, further activate the enzyme system, thereby activating bone or cartilage cells, which is beneficial to the growth of bone cells and promotes fracture healing. In addition, the body's tissues and blood contain a variety of metal elements and inorganic salts such as potassium, sodium, and iron. Blood vessels and blood are also conductors. When the magnetic field acts on the conductor, microcurrents will be generated, causing changes in ion concentration and speed, strengthening the exchange of substances inside and outside the cells, which is beneficial to the growth of bone cells and promotes fracture healing; (3) When ultrasound acts on ultrasonic controlled release drug-loaded microspheres, ultrasound can enhance blood circulation, improve the local microenvironment, activate cell activity, and prepare for the subsequent bone repair process; 3. Controllable drug release mechanism and stable and continuous dual sustained-release system: (1) Controllable drug release mechanism: The ultrasound-controlled drug-loaded microspheres contained in this design can be quickly released under ultrasound conditions, which can be used for analgesia, anti-inflammation and infection prevention in patients in the early stage of fracture, and slowly released under natural non-ultrasonic conditions, which can be used to maintain and preserve the healthy microenvironment homeostasis throughout the bone repair process; (2) Stable and continuous dual sustained-release system: Both microspheres and hydrogels are sustained-release structures, and this design embeds microspheres in hydrogels to establish a dual sustained-release system, making drug release more stable, continuous and reliable; (3) The two types of microspheres are independent of each other and do not interfere with each other, avoiding the interaction between drugs and active substances before injection, which reduces the therapeutic effect; 4. Multifunctionality: (1) Adhesion: The addition of polydopamine methacrylamide can improve the adhesion of the composite hydrogel, thereby enhancing the contact and bonding between the composite hydrogel and bone tissue, promoting the adhesion and growth of bone cells, improving mechanical properties and support, and promoting angiogenesis and nutrient supply, which is beneficial to promoting bone healing; (2) Antioxidant property: The addition of catalase can improve the antioxidant property of the composite hydrogel, reduce the level of high reactive oxygen, quickly induce the decomposition of H2O2 and produce oxygen, relieve oxidative stress and solve the problem of hypoxia, which is beneficial to promoting bone healing; (3) Weak magnetism: The addition of magnetic nanoparticles can enable the composite hydrogel to exert a continuous weak magnetic force on cells, enhance local drug release, improve the mechanical properties of the hydrogel, and promote bone healing; (4) Antibacterial property: The addition of drugs can provide a stable environment, which is beneficial to promoting bone healing; (5) Development property: Magnetic nanoparticles have magnetism and can be used as auxiliary contrast agents in magnetic resonance imaging (MRI), making imaging clearer. This allows researchers to monitor the localization, distribution and degradation of the hydrogel and its drug delivery system in the body during bone healing in real time, thereby better evaluating the therapeutic effect. Magnetic resonance imaging can provide a more accurate assessment of bone healing progress and further optimize treatment plans. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Schematic diagram of the preparation process of ultrasound-controlled release drug-loaded microspheres Figure 2 Schematic diagram of the preparation process of functional calcium carbonate porous microspheres Figure 3 Schematic diagram of the preparation process of hydrogel Figure 4 The results of the evaluation of the in vitro natural sustained release effect of functional substances in hydrogels Figure 5 The results of the ultrasonic controlled release evaluation of diclofenac sodium in hydrogel Figure 6 The results of the in vivo biodegradation evaluation are shown in Figure 2. Figure 7 Figure 2 shows the bone volume fraction test results. Figure 8 Bone mineral density test results Figure reference numerals: 1, organic phase, 2, aqueous phase, 3, emulsion, 4, syringe, 5, ultrasound, 6, electric field, 7, baffle, 8, ultrasound-controlled release drug-loaded microspheres, 9, anhydrous sodium carbonate solution, 10, calcium chloride solution, 11, active factor, 12, functional calcium carbonate porous microspheres, 13, methacrylated gelatin solution, 14, nanoclay, 15, calcium phosphate bone cement, 16, magnetic nanoparticles, 17, catalase, 18, polydopamine methacrylamide, A, hydrogel, DETAILED DESCRIPTION

[0014] The technical scheme of the present invention is further described in detail below in conjunction with embodiments and comparative examples, but the present invention is not limited to these specific embodiments.

[0015] The following are examples and comparative examples:

[0016] Example 1 (1) Preparation of ultrasonic controlled release drug-loaded microspheres 8: 3% diclofenac sodium and 3% polyvinyl pyrrolidone were added to 30% polylactic acid-glycolic acid chloroform solution, and stirred in an ice-water environment for 15 min to obtain an organic phase 1; then the organic phase 1 was slowly added dropwise to a 3% polyvinyl alcohol aqueous phase 2, and emulsified for 20 min under 500w ultrasound and 4000rpm high-speed stirring to obtain an emulsion 3; the emulsion 3 was placed in a syringe 4, and a constant flow rate of 1.0mL / h, an ultrasonic power of 100w, and an applied voltage of 8kV were set, and sprayed and granulated in a nitrogen environment, and collected in a baffle 7 with a distance of 20cm from the nozzle tip of the syringe 4, and vacuum freeze-dried for 30h to obtain ultrasonic controlled release drug-loaded microspheres 8; (2) Preparation of functional porous calcium carbonate microspheres 12: 35% anhydrous sodium carbonate solution 9 and 35% calcium chloride solution 10 were added in a volume ratio of 1:1, ultrasonically stirred at 500W for 15min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed three times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; calcium carbonate porous microspheres and bone morphogenetic protein 2 were added to PBS (pH 7.4) in a mass ratio of 1000:3, gently stirred at 500W for 36h in an ice water and nitrogen environment, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres 12; (3) Preparation of hydrogel A: Nanoclay 14 powder and calcium phosphate cement 15 powder were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in a mass ratio of 1:2, and gently stirred at 50 rpm for 20 min under 250 W ultrasound to obtain a mixed solution a; under the condition of gentle stirring at 50 rpm, magnetic nanoparticles 16, catalase 17, polydopamine methacrylamide 18, ultrasound-controlled release drug-loaded microspheres 8 and functional calcium carbonate porous microspheres 12 were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in sequence, and gently stirred at 50 rpm for 20 min to obtain a mixed solution b; the mixed solution a and the mixed solution b were added and mixed in a volume ratio of 1:1, and gently stirred at 50 rpm for 20 min to obtain a mixed solution c; the mixed solution c was polymerized under blue light with a wavelength of 405 nm for 30 s, and the hydrogel A was collected.

[0017] Example 2 (1) Preparation of ultrasonic controlled release drug-loaded microspheres 8: 5% diclofenac sodium and 5% polyvinyl pyrrolidone were added to 50% polylactic acid-glycolic acid chloroform solution, and stirred in an ice-water environment for 20 min to obtain an organic phase 1; then the organic phase 1 was slowly added dropwise to a 5% polyvinyl alcohol aqueous phase 2, and emulsified for 30 min under 1000w ultrasound and 5000rpm high-speed stirring to obtain an emulsion 3; the emulsion 3 was placed in a syringe 4, and a constant flow rate of 1.4mL / h, an ultrasonic power of 200w, and an applied voltage of 10kV were set, and spray granulation was performed in a nitrogen environment, and the emulsion was collected in a baffle 7 with a distance of 22cm from the nozzle tip of the syringe 4, and vacuum freeze-dried for 36h to obtain ultrasonic controlled release drug-loaded microspheres 8; (2) Preparation of functional porous calcium carbonate microspheres 12: 40% anhydrous sodium carbonate solution 9 and 40% calcium chloride solution 10 were added in a volume ratio of 1:1, ultrasonically stirred at 1000W for 20 min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed three times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; calcium carbonate porous microspheres and bone morphogenetic protein 2 were added to PBS (pH 7.4) in a mass ratio of 1000:5, gently stirred at 1000W for 48 h in an ice water and nitrogen environment, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres 12; (3) Preparation of hydrogel A: Nanoclay 14 powder and calcium phosphate cement 15 powder were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in a mass ratio of 1:3, and gently stirred at 100 rpm for 25 min under 500 W ultrasound to obtain a mixed solution a; under the condition of gentle stirring at 100 rpm, magnetic nanoparticles 16, catalase 17, polydopamine methacrylamide 18, ultrasound-controlled release drug-loaded microspheres 8 and functional calcium carbonate porous microspheres 12 were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in sequence, and gently stirred at 100 rpm for 25 min to obtain a mixed solution b; mixed solution a and mixed solution b were added in a volume ratio of 1:1.5 and gently stirred at 100 rpm for 25 min to obtain a mixed solution c; mixed solution c was polymerized under 405 nm wavelength blue light for 40 s, and hydrogel A was obtained.

[0018] Example 3 (1) Preparation of ultrasonic controlled release drug-loaded microspheres 8: 1% diclofenac sodium and 1% polyvinyl pyrrolidone were added to 10% polylactic acid-glycolic acid chloroform solution, and stirred in an ice-water environment for 10 min to obtain an organic phase 1; then the organic phase 1 was slowly added dropwise to a 1% polyvinyl alcohol aqueous phase 2, and emulsified for 10 min under 10W ultrasound and 3000rpm high-speed stirring to obtain an emulsion 3; the emulsion 3 was placed in a syringe 4, and a constant flow rate of 0.6mL / h, an ultrasonic power of 10W, and an applied voltage of 6kV were set, and sprayed and granulated in a nitrogen environment, and collected in a baffle 7 with a distance of 18cm from the nozzle tip of the syringe 4, and vacuum freeze-dried for 24h to obtain ultrasonic controlled release drug-loaded microspheres 8; (2) Preparation of functional porous calcium carbonate microspheres 12: 30% anhydrous sodium carbonate solution 9 and 30% calcium chloride solution 10 were added in a volume ratio of 1:1, and ultrasonically stirred at 10W for 10 min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed three times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; calcium carbonate porous microspheres and bone morphogenetic protein 2 were added to PBS (pH 7.4) in a mass ratio of 1000:1, and gently stirred at 10W for 24 h in an ice water and nitrogen environment, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres 12; (3) Preparation of hydrogel A: Nanoclay 14 powder and calcium phosphate cement 15 powder were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in a mass ratio of 1:1, and gently stirred at 10 rpm for 15 min under 10 W ultrasound to obtain a mixed solution a; under the condition of gentle stirring at 10 rpm, magnetic nanoparticles 16, catalase 17, polydopamine methacrylamide 18, ultrasound-controlled release drug-loaded microspheres 8 and functional calcium carbonate porous microspheres 12 were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in sequence, and gently stirred at 10 rpm for 15 min to obtain a mixed solution b; mixed solution a and mixed solution b were added and mixed in a volume ratio of 1:0.5, and gently stirred at 10 rpm for 15 min to obtain a mixed solution c; mixed solution c was polymerized under 405 nm wavelength blue light for 20 s, and hydrogel A was obtained.

[0019] Example 4 (1) Preparation of ultrasonic controlled release drug-loaded microspheres 8: 1% diclofenac sodium and 3% polyvinyl pyrrolidone were added to 10% polylactic acid-glycolic acid chloroform solution, and stirred in an ice-water environment for 15 min to obtain an organic phase 1; then the organic phase 1 was slowly added dropwise to a 3% polyvinyl alcohol aqueous phase 2, and emulsified for 10 min under 100W ultrasound and 5000rpm high-speed stirring to obtain an emulsion 3; the emulsion 3 was placed in a syringe 4, and a constant flow rate of 1.0mL / h, an ultrasonic power of 100W, and an applied voltage of 8kV were set, and sprayed and granulated in a nitrogen environment, and collected in a baffle 7 with a distance of 22cm from the nozzle tip of the syringe 4, and vacuum freeze-dried for 30h to obtain ultrasonic controlled release drug-loaded microspheres 8; (2) Preparation of functional porous calcium carbonate microspheres 12: 30% anhydrous sodium carbonate solution 9 and 30% calcium chloride solution 10 were added in a volume ratio of 1:1, ultrasonically stirred at 1000W for 15 min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed three times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; calcium carbonate porous microspheres and bone morphogenetic protein 2 were added to PBS (pH 7.4) in a mass ratio of 1000:1, gently stirred at 10W in an ice water and nitrogen environment for 48 h, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres 12; (3) Preparation of hydrogel A: Nanoclay 14 powder and calcium phosphate cement 15 powder were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in a mass ratio of 1:1, and gently stirred at 500W ultrasonic and 50rpm for 20min to obtain a mixed solution a; under the condition of gentle stirring at 50rpm, magnetic nanoparticles 16, catalase 17, polydopamine methacrylamide 18, ultrasound-controlled release drug-loaded microspheres 8 and functional calcium carbonate porous microspheres 12 were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in sequence, and gently stirred at 10rpm for 25min to obtain a mixed solution b; mixed solution a and mixed solution b were added and mixed in a volume ratio of 1:0.5, and gently stirred at 100rpm for 25min to obtain a mixed solution c; mixed solution c was polymerized under blue light with a wavelength of 405nm for 30s, and hydrogel A was obtained.

[0020] Example 5 (1) Preparation of ultrasonic controlled release drug-loaded microspheres 8: 3% diclofenac sodium and 5% polyvinyl pyrrolidone were added to 30% polylactic acid-glycolic acid chloroform solution, and stirred in an ice-water environment for 10 min to obtain an organic phase 1; then the organic phase 1 was slowly added dropwise to a 5% polyvinyl alcohol aqueous phase 2, and emulsified for 20 min under 500w ultrasound and 4000rpm high-speed stirring to obtain an emulsion 3; the emulsion 3 was placed in a syringe 4, and a constant flow rate of 0.6mL / h, an ultrasonic power of 100w, and an applied voltage of 10kV were set, and spray granulation was performed in a nitrogen environment, and the emulsion was collected in a baffle 7 with a distance of 20cm from the nozzle tip of the syringe 4, and vacuum freeze-dried for 36h to obtain ultrasonic controlled release drug-loaded microspheres 8; (2) Preparation of functional porous calcium carbonate microspheres 12: 40% anhydrous sodium carbonate solution 9 and 40% calcium chloride solution 10 were added in a volume ratio of 1:1, ultrasonically stirred at 500W for 20min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed three times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; calcium carbonate porous microspheres and bone morphogenetic protein 2 were added to PBS (pH 7.4) in a mass ratio of 1000:5, gently stirred at 1000W for 36h in an ice water and nitrogen environment, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres 12; (3) Preparation of hydrogel A: Nanoclay 14 powder and calcium phosphate cement 15 powder were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in a mass ratio of 1:2, and gently stirred at 500W ultrasonic at 10rpm for 15min to obtain a mixed solution a; magnetic nanoparticles 16, catalase 17, polydopamine methacrylamide 18, ultrasonic controlled release drug-loaded microspheres 8 and functional calcium carbonate porous microspheres 12 were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in sequence under gentle stirring at 100rpm, and gently stirred at 10rpm for 25min to obtain a mixed solution b; mixed solution a and mixed solution b were added in a volume ratio of 1:1 and gently stirred at 50rpm for 15min to obtain a mixed solution c; mixed solution c was polymerized under 405nm wavelength blue light for 20s, and hydrogel A was obtained.

[0021] Example 6 (1) Preparation of ultrasonic controlled release drug-loaded microspheres 8: 5% diclofenac sodium and 1% polyvinyl pyrrolidone were added to 50% polylactic acid-glycolic acid chloroform solution, and stirred in an ice-water environment for 20 min to obtain an organic phase 1; then the organic phase 1 was slowly added dropwise to a 1% polyvinyl alcohol aqueous phase 2, and emulsified for 30 min under 1000w ultrasound and 5000rpm high-speed stirring to obtain an emulsion 3; the emulsion 3 was placed in a syringe 4, and a constant flow rate of 1.4mL / h, an ultrasonic power of 50w, and an applied voltage of 6kV were set, and sprayed and granulated in a nitrogen environment, and collected in a baffle 7 with a distance of 18cm from the nozzle tip of the syringe 4, and vacuum freeze-dried for 24h to obtain ultrasonic controlled release drug-loaded microspheres 8; (2) Preparation of functional porous calcium carbonate microspheres 12: 40% anhydrous sodium carbonate solution 9 and 35% calcium chloride solution 10 were added in a volume ratio of 1:1, ultrasonically stirred at 500W for 10 min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed three times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; calcium carbonate porous microspheres and bone morphogenetic protein 2 were added to PBS (pH 7.4) in a mass ratio of 1000:3, gently stirred at 500W for 24 h in an ice water and nitrogen environment, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres 12; (3) Preparation of hydrogel A: Nanoclay 14 powder and calcium phosphate cement 15 powder were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in a mass ratio of 1:3, and gently stirred at 50 rpm for 25 min under 250 W ultrasound to obtain a mixed solution a; magnetic nanoparticles 16, catalase 17, polydopamine methacrylamide 18, ultrasound-controlled release drug-loaded microspheres 8 and functional calcium carbonate porous microspheres 12 were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in sequence under gentle stirring at 10 rpm, and gently stirred at 100 rpm for 25 min to obtain a mixed solution b; mixed solution a and mixed solution b were added and mixed in a volume ratio of 1:1.5, and gently stirred at 50 rpm for 15 min to obtain a mixed solution c; mixed solution c was polymerized under 405 nm wavelength blue light for 20 s, and hydrogel A was collected.

[0022] Example 7 (1) Preparation of ultrasonic controlled release drug-loaded microspheres 8: 1% diclofenac sodium and 3% polyvinyl pyrrolidone were added to 30% polylactic acid-glycolic acid chloroform solution, and stirred in an ice-water environment for 15 min to obtain an organic phase 1; then the organic phase 1 was slowly added dropwise to a 1% polyvinyl alcohol aqueous phase 2, and emulsified for 30 min under 1000w ultrasound and 3000rpm high-speed stirring to obtain an emulsion 3; the emulsion 3 was placed in a syringe 4, and a constant flow rate of 1.4mL / h, an ultrasonic power of 200w, and an applied voltage of 8kV were set, and sprayed and granulated in a nitrogen environment, and collected in a baffle 7 with a distance of 18cm from the nozzle tip of the syringe 4, and vacuum freeze-dried for 30h to obtain ultrasonic controlled release drug-loaded microspheres 8; (2) Preparation of functional porous calcium carbonate microspheres 12: 35% anhydrous sodium carbonate solution 9 and 35% calcium chloride solution 10 were added in a volume ratio of 1:1, and ultrasonically stirred at 10W for 15 min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed three times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; calcium carbonate porous microspheres and bone morphogenetic protein 2 were added to PBS (pH 7.4) in a mass ratio of 1000:3, and gently stirred at 500W for 36 h in an ice water and nitrogen environment, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres 12; (3) Preparation of hydrogel A: Nanoclay 14 powder and calcium phosphate cement 15 powder were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in a mass ratio of 1:2, and gently stirred at 100 rpm for 15 min under 250 W ultrasound to obtain a mixed solution a; under the condition of gentle stirring at 100 rpm, magnetic nanoparticles 16, catalase 17, polydopamine methacrylamide 18, ultrasound-controlled release drug-loaded microspheres 8 and functional calcium carbonate porous microspheres 12 were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in sequence, and gently stirred at 50 rpm for 25 min to obtain a mixed solution b; mixed solution a and mixed solution b were added and mixed in a volume ratio of 1:0.5, and gently stirred at 10 rpm for 25 min to obtain a mixed solution c; mixed solution c was polymerized under blue light with a wavelength of 405 nm for 40 s, and hydrogel A was obtained.

[0023] Example 8 (1) Preparation of ultrasonic controlled release drug-loaded microspheres 8: 1% diclofenac sodium and 3% polyvinyl pyrrolidone were added to 30% polylactic acid-glycolic acid chloroform solution, and stirred in an ice-water environment for 15 min to obtain an organic phase 1; then the organic phase 1 was slowly added dropwise to a 1% polyvinyl alcohol aqueous phase 2, and emulsified for 30 min under 1000w ultrasound and 3000rpm high-speed stirring to obtain an emulsion 3; the emulsion 3 was placed in a syringe 4, and a constant flow rate of 1.4mL / h, an ultrasonic power of 200w, and an applied voltage of 8kV were set, and sprayed and granulated in a nitrogen environment, and collected in a baffle 7 with a distance of 18cm from the nozzle tip of the syringe 4, and vacuum freeze-dried for 30h to obtain ultrasonic controlled release drug-loaded microspheres 8; (2) Preparation of functional porous calcium carbonate microspheres 12: 40% anhydrous sodium carbonate solution 9 and 35% calcium chloride solution 10 were added in a volume ratio of 1:1, ultrasonically stirred at 500W for 10 min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed three times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; calcium carbonate porous microspheres and bone morphogenetic protein 2 were added to PBS (pH 7.4) in a mass ratio of 1000:3, gently stirred at 500W for 24 h in an ice water and nitrogen environment, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres 12; (3) Preparation of hydrogel A: Nanoclay 14 powder and calcium phosphate cement 15 powder were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in a mass ratio of 1:2, and gently stirred at 50 rpm for 25 min under 250 W ultrasound to obtain a mixed solution a; magnetic nanoparticles 16, catalase 17, polydopamine methacrylamide 18, ultrasound-controlled release drug-loaded microspheres 8 and functional calcium carbonate porous microspheres 12 were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in sequence under gentle stirring at 10 rpm, and gently stirred at 50 rpm for 25 min to obtain a mixed solution b; mixed solution a and mixed solution b were added and mixed in a volume ratio of 1:1, and gently stirred at 50 rpm for 25 min to obtain a mixed solution c; mixed solution c was polymerized under 405 nm wavelength blue light for 30 s, and hydrogel A was obtained.

[0024] Comparative Example 1 Comparative Example 1 is substantially the same as Example 1, except that in Comparative Example 1, only nanoclay 14 is added, and calcium phosphate bone cement 15 is not added.

[0025] Comparative Example 2 Comparative Example 2 is substantially the same as Example 1, except that in Comparative Example 2, only calcium phosphate bone cement 15 is added, and nanoclay 14 is not added.

[0026] Comparative Example 3 Comparative Example 3 is substantially the same as Example 1, except that: in Comparative Example 3, no ultrasonic controlled-release drug-loaded microspheres 8 are added.

[0027] Comparative Example 4 Comparative Example 4 is substantially the same as Example 1, except that no functional porous calcium carbonate microspheres 12 are added in Comparative Example 4.

[0028] Comparative Example 5 Comparative Example 5 is substantially the same as Example 1, except that catalase 17 is not added in Comparative Example 5.

[0029] Comparative Example 6 Comparative Example 6 is substantially the same as Example 1, except that no magnetic nanoparticles 16 are added in Comparative Example 6.

[0030] Comparative Example 7 Comparative Example 7 is substantially the same as Example 1, except that polydopamine methacrylamide 18 is not added in Comparative Example 7.

[0031] Comparative Example 8 (1) Preparation of ultrasonic controlled release drug-loaded microspheres 8: 0.5% analgesic and anti-inflammatory drugs and 0.5% emulsifier were added to 5% polylactic acid-glycolic acid organic solution, and stirred in an ice-water environment for 5 min to obtain an organic phase 1; then the organic phase 1 was slowly added dropwise to 0.5% polyvinyl alcohol aqueous phase 2, and emulsified for 5 min under 1500w ultrasound and 2000rpm high-speed stirring to obtain emulsion 3; the emulsion 3 was placed in a syringe 4, set at a constant flow rate of 0.5mL / h, 300w ultrasonic power and 20kV applied voltage, sprayed and granulated in a nitrogen environment, and collected in a baffle 7 with a distance of 30cm from the nozzle tip of the syringe 4, and vacuum freeze-dried for 10h to obtain ultrasonic controlled release drug-loaded microspheres 8; (2) Preparation of functional porous calcium carbonate microspheres 12: 20% anhydrous sodium carbonate solution 9 and 20% calcium chloride solution 10 were added in a volume ratio of 1:1, ultrasonically stirred at 2000W for 5 min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed three times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; calcium carbonate porous microspheres and bone morphogenetic protein 2 were added to PBS (pH 7.4) in a mass ratio of 1000:7, gently stirred at 2000W for 10 h in an ice water and nitrogen environment, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres 12; (3) Preparation of hydrogel A: Nanoclay 14 powder and calcium phosphate cement 15 powder were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in a mass ratio of 1:5, and stirred at 200 rpm for 60 min under 1000 W ultrasonic wave to obtain a mixed solution a; magnetic nanoparticles 16, catalase 17, polydopamine methacrylamide 18, ultrasonic controlled release drug-loaded microspheres 8 and functional calcium carbonate porous microspheres 12 were added to 5% methacrylated gelatin solution 13 containing 0.25% photoinitiator in sequence under gentle stirring at 200 rpm, and continued to be gently stirred at 200 rpm for 5 min to obtain a mixed solution b; mixed solution a and mixed solution b were added and mixed in a volume ratio of 1:0.1, and continued to be gently stirred at 200 rpm for 5 min to obtain a mixed solution c; mixed solution c was polymerized under 405 nm wavelength blue light for 5 s, and collected to obtain hydrogel A.

[0032] The following method is used to detect hydrogel A in the present invention: 1. Antibacterial Sterile LB broth medium was used to culture bacteria (Staphylococcus aureus), and pure bacterial solution was used as the control group. The absorbance of the embodiment and the comparison group at a wavelength of 600 nm was measured respectively, and the relative inhibition rate was calculated as [(control − sample) control] × 100%; 2. In vitro release effect evaluation test of functional substances (tested using Example 1 as a sample) (1) Drug release: Using diclofenac sodium as the test object, ultrasonic controlled release and natural sustained release were measured; (2) Active factor release: bone morphogenetic protein 2 was used as the test object and measured using a protein assay kit; (3) Ion release: measured by inductively coupled plasma mass spectrometry; 3. Adhesion By sticking hydrogel A on the surface of pig bones, and then turning the pig bones over, observe whether hydrogel A can stay on within 1 minute; 4. Antioxidant The antioxidant activity of hydrogel A was evaluated by measuring the DCF fluorescence intensity using a reactive oxygen species assay kit; 5. Biocompatibility The test items include cytotoxicity, sensitization reaction, intradermal reaction, pyrogenicity and acute systemic toxicity, and the test methods are carried out in accordance with GB16886; 6. Animal experiments (1) In vivo biodegradation effect evaluation test of hydrogel A: hydrogel A was implanted subcutaneously on the back of rats and tested by weighing method; (2) In vivo osteogenesis evaluation test: The in vivo osteogenesis effect was evaluated by calculating the bone volume fraction (BV / TV) and bone mineral density (BMD); 7. Bone repair Imaging X-ray examination.

[0033] Hydrogel A was tested according to the above test methods, and the results are shown in Table 1. Figure 4~Figure 8 shown.

[0034] Table 1 Test results of embodiments and comparative examples

[0035]

[0036] By comparing Table 1, Figure 4~Figure 8 Analysis shows that the hydrogel A designed in the present invention has good material controlled release and sustained release, can avoid infection, reduce the level of reactive oxygen, has good biocompatibility and adhesion, and its biodegradability can bionic match the bone repair process, and the degradation products further synergistically promote bone repair.

[0037] From the comparison between Example 1 and Comparative Example 1, it can be seen that only containing nanoclay 14 but not calcium phosphate bone cement 15 causes the degradation rate of hydrogel A to be too fast, which does not match the bone repair rate, and ultimately leads to poor bone repair; From the comparison between Example 1 and Comparative Example 2, it can be seen that only calcium phosphate bone cement 15 is contained without nanoclay 14, resulting in the hydrogel A degrading too slowly, which does not match the bone repair speed, and ultimately leads to poor bone repair. From the comparison between Example 1 and Comparative Example 3, it can be seen that without the ultrasound controlled release drug-loaded microspheres 8, the controlled release cannot be achieved by combining ultrasound, and it cannot be used for on-demand controlled release of drugs in the acute phase, and the functionality is poor, and ultimately the bone repair is poor due to infection; From the comparison between Example 1 and Comparative Example 4, it can be seen that without the functional calcium carbonate porous microspheres 12, active factors and calcium ions cannot be effectively provided during the critical time of bone tissue formation, which will cause poor bone tissue formation and poor bone repair. From the comparison between Example 1 and Comparative Example 5, it can be seen that without catalase 17, the level of active oxygen in the body cannot be reduced, thus ultimately affecting bone repair; From the comparison between Example 1 and Comparative Example 6, it can be seen that without the nanomagnetic particles 16, a micromagnetic field cannot be formed, and synergistic enhancement cannot be achieved to promote bone repair; From the comparison between Example 1 and Comparative Example 7, it can be seen that without polydopamine methacrylamide 18, it cannot adhere to the affected area and may fall off, ultimately affecting bone repair; From the comparison between Example 1 and Comparative Example 8, it can be seen that when the preparation process parameters are not appropriate, various test indicators are not ideal.

[0038] The results show that the hydrogel A designed in the present invention has good properties and clinical application value.

[0039] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention can be made, and any changes that can be thought of by those skilled in the art should be within the scope of protection of the present invention.

Claims

1. A functional injectable biomimetic hydrogel for promoting bone healing, characterized in that: The hydrogel has good biodegradability, biocompatibility, adhesion, antioxidant properties, weak magnetism and developing properties. It is a bionic material based on methacrylated gelatin, embedded with 1-5% ultrasonic controlled release drug-loaded microspheres and 1-5% functional calcium carbonate porous microspheres, as well as 5-10% nanoclay, 10-20% calcium phosphate bone cement, 1-5% magnetic nanoparticles and 1-5% peroxidase; the antioxidant property is achieved by the peroxidase in the hydrogel by reducing the high active oxygen level at the bone healing site; the weak magnetism is generated by the 1-5% magnetic nanoparticles in the hydrogel, and can cooperate with the external magnetic field to promote bone healing; the visualization property refers to the use of magnetic nanoparticles as auxiliary contrast agents in magnetic resonance imaging using their weak magnetism, making imaging clearer and convenient for real-time observation and research; the ultrasonic controlled release drug-loaded microspheres are biodegradable microspheres that respond to ultrasound waves of a specific frequency and are prepared by an emulsification process and an ultrasonic voltage spraying process, with a particle size of 5-25 μm; the functional calcium carbonate porous microspheres are loaded microspheres formed by loading active factors into calcium carbonate porous microspheres, with a particle size of 1-13 μm, and can slowly release calcium ions and active factors; the content ratio of the nanoclay and calcium phosphate bone cement in the hydrogel is 1:1-3; The preparation method comprises the following steps: (1) Preparation of ultrasonic controlled release drug-loaded microspheres: 1-5% analgesic and anti-inflammatory drugs and 1-5% emulsifier are added to 10-50% polylactic acid-glycolic acid organic solution, stirred in an ice water environment for 10-20 minutes to obtain an organic phase; then the organic phase is slowly added dropwise to 1-5% polyvinyl alcohol aqueous phase, emulsified for 10-30 minutes under 10-1000w ultrasound and 3000-5000rpm high-speed stirring to obtain an emulsion; the emulsion is placed in a syringe, set a constant flow rate of 0.6-1.4mL / h, an ultrasonic power of 10-200w and an applied voltage of 6-10kV, spray granulation in a nitrogen environment, and collected in a baffle with a distance of 18-22cm from the tip of the syringe nozzle, and vacuum freeze-dried for 24-36h to obtain ultrasonic controlled release drug-loaded microspheres; (2) Preparation of functional porous calcium carbonate microspheres: 30-40% anhydrous sodium carbonate solution and 30-40% calcium chloride solution were added in a volume ratio of 1:1, ultrasonically stirred at 10-1000w for 10-20min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed 3 times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; the porous calcium carbonate microspheres and active factors were added to PBS (pH 7.4) in a mass ratio of 1000:1-5, gently stirred at 10-1000w in an ice water and nitrogen environment for 24-48h, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres; (3) Preparation of hydrogel: Add nanoclay powder and calcium phosphate bone cement powder in a mass ratio of 1:1-3 to a 5% methacrylated gelatin solution containing 0.25% photoinitiator, and stir gently at 10-500w ultrasonic for 15-25min to obtain a mixed solution a; under gentle stirring conditions, magnetic nanoparticles, catalase, polydopamine methacrylamide, ultrasound-controlled release drug-loaded microspheres and functional calcium carbonate porous microspheres are added slowly and continuously to a 5% methacrylated gelatin solution containing 0.25% photoinitiator, and continue to stir gently for 15-25min to obtain a mixed solution b; mix the mixed solution a and the mixed solution b in a volume ratio of 1:0.5-1.5, and continue to stir gently for 15-25min to obtain a mixed solution c; place the mixed solution c under 405nm wavelength blue light for polymerization for 20-40s, and collect to obtain a hydrogel.

2. The functional injectable biomimetic hydrogel for promoting bone healing according to claim 1, characterized in that: The ultrasonic voltage spraying process is a technology for preparing microspheres by spraying the emulsion onto the baffle in a coordinated environment of 10-200w ultrasonic waves combined with 6-10kV applied voltage.

3. The functional injectable biomimetic hydrogel for promoting bone healing according to claim 1, characterized in that: The nano clay is one of montmorillonite, bentonite, kaolin and lattite.

4. The functional injectable biomimetic hydrogel for promoting bone healing according to claim 1, characterized in that: The active factor is one of bone morphogenetic protein, fibroblast growth factor, platelet-derived growth factor, transforming growth factor β, vascular endothelial growth factor, insulin-like growth factor, chondrocyte growth factor and extracellular matrix protein.

5. A method for preparing a functional injectable bionic hydrogel for promoting bone healing according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Preparation of ultrasonic controlled release drug-loaded microspheres: 1-5% analgesic and anti-inflammatory drugs and 1-5% emulsifier are added to 10-50% polylactic acid-glycolic acid organic solution, stirred in an ice water environment for 10-20 minutes to obtain an organic phase; then the organic phase is slowly added dropwise to 1-5% polyvinyl alcohol aqueous phase, emulsified for 10-30 minutes under 10-1000w ultrasound and 3000-5000rpm high-speed stirring to obtain an emulsion; the emulsion is placed in a syringe, set a constant flow rate of 0.6-1.4mL / h, an ultrasonic power of 10-200w and an applied voltage of 6-10kV, spray granulation in a nitrogen environment, and collected in a baffle with a distance of 18-22cm from the tip of the syringe nozzle, and vacuum freeze-dried for 24-36h to obtain ultrasonic controlled release drug-loaded microspheres; (2) Preparation of functional porous calcium carbonate microspheres: 30-40% anhydrous sodium carbonate solution and 30-40% calcium chloride solution were added in a volume ratio of 1:1, ultrasonically stirred at 10-1000w for 10-20min in a nitrogen environment, collected by low-temperature centrifugation at 4°C, washed 3 times with 50% ethanol solution, and collected after vacuum freeze-drying and stored at 4°C in the dark to obtain porous calcium carbonate microspheres; the porous calcium carbonate microspheres and active factors were added to PBS (pH 7.4) in a mass ratio of 1000:1-5, gently stirred at 10-1000w in an ice water and nitrogen environment for 24-48h, collected by low-temperature centrifugation at 4°C and stored at 4°C in the dark to obtain functional porous calcium carbonate microspheres; (3) Preparation of hydrogel: Add nanoclay powder and calcium phosphate bone cement powder in a mass ratio of 1:1-3 to a 5% methacrylated gelatin solution containing 0.25% photoinitiator, and stir gently at 10-500w ultrasonic for 15-25min to obtain a mixed solution a; under gentle stirring conditions, magnetic nanoparticles, catalase, polydopamine methacrylamide, ultrasound-controlled release drug-loaded microspheres and functional calcium carbonate porous microspheres are added slowly and continuously to a 5% methacrylated gelatin solution containing 0.25% photoinitiator, and continue to stir gently for 15-25min to obtain a mixed solution b; mix the mixed solution a and the mixed solution b in a volume ratio of 1:0.5-1.5, and continue to stir gently for 15-25min to obtain a mixed solution c; place the mixed solution c under 405nm wavelength blue light for polymerization for 20-40s, and collect to obtain a hydrogel.

6. The method for preparing the functional injectable biomimetic hydrogel for promoting bone healing according to claim 5, characterized in that: In step (1), the analgesic and anti-inflammatory drug is one of diclofenac sodium and lidocaine; and the emulsifier is one of polyvinyl pyrrolidone, Tween-80, and Span-80.

7. The method for preparing the functional injectable biomimetic hydrogel for promoting bone healing according to claim 5, characterized in that: The mass ratio of the analgesic and anti-inflammatory drug to polylactic acid-glycolic acid in step (1) is 1:10-50.

8. The method for preparing the functional injectable biomimetic hydrogel for promoting bone healing according to claim 5, characterized in that: The vacuum freeze-drying time in step (2) is 24-36 hours.

9. The method for preparing the functional injectable bionic hydrogel for promoting bone healing according to claim 5, characterized in that: The photoinitiator in step (3) is phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, and the mass ratio of magnetic nanoparticles and catalase added is 1:0.5-1.

5.

10. The method for preparing the functional injectable biomimetic hydrogel for promoting bone healing according to claim 5, characterized in that: In step (3), the polydopamine methacrylamide is added at a concentration of 0.1-0.5%, the mass ratio of ultrasonic controlled release drug-loaded microspheres to functional calcium carbonate porous microspheres is 1:0.5-1.5, and the speed of gentle stirring is 10-100 rpm.

Citation Information

Patent Citations

  • Viscoelastic hydrogel complex for promoting bone defect healing, preparation and application

    CN118718104A

  • Dispersant's with multiple aromatic imide anchor groups

    CN105849210A

  • Composite hydrogel for promoting osteomyelitis healing and preparation method thereof

    CN110935066A

  • Preparation method of temperature-magnetic field synergistic response drug release calcium phosphate-based bone cement

    CN112618789A

  • Calcilytic compounds

    SG142680A1

Cited By

  • Nano-particles, slow-release hydrogel containing nano-particles and ultrasonic system and application of nano-particles and slow-release hydrogel

    CN120617501A

  • Hydrogel microneedle with biocompatibility and mechanical strength as well as preparation method and application of hydrogel microneedle

    CN120899617A

  • Organic-inorganic composite gel material as well as preparation method and application thereof

    CN122342856A